Comparison of freestyle race between elite junior and senior swimmers - Nomura, T.; Wakayoshi, K.; Okuno, K.; Miyashita, M. (2000)
The purpose of this study was to evaluate the differences in freestyle race parameters between elite junior swimmers and the elite senior swimmers. The subjects were 473 male finalists of freestyle events in Japanese swimming championships from '94 to '99. The subjects were classified under the junior (Jr: Under high-school age, n=65) and the senior (Sr: Over college age, n=408). Race parameters included event record, start, turn, finish, swimming velocity, stroke rate, and stroke length. The finalists contained a percentage of Jr was increased 7.0% to 24.5% as event distance extended 50m to 1500m. The event records of Jr were significantly slower than Sr on 50m, 100m, and 200m events. However, on 400m and 1500m events, there was no significant difference. The starting time of Jr was significantly longer than Sr during 50m event. The turning out time of Jr was significantly longer than Sr during 100m, 200m and 400m events. The swimming velocity of Jr was significantly lower than Sr during whole 100m event, the first half of 200m and 400m events, and the last 200m of 1500m event. The stroke rate of Jr was lower than Sr during 100m event. It seemed that a physical resource of the junior swimmer was not contented with short distance events. More muscle power, agility and gliding skill are necessary. Although the aerobic ability of the junior swimmer has already developed for middle/long distance events, the anaerobic ability has a room for improvement. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science 7-13 September - Brisbane, Australia 2000)